Management Innovation: Shaping the future of Business Management - Abdullaeva, Yulduzkhon (MMIT Proceedings, 2025)
In today’s fast-changing business world, traditional management approaches are no longer enough. To stay competitive and resilient, organizations need to embrace innovation not just in products, but in how they manage people, processes, and strategies. This article looks at what managerial innovation really means-bringing in new ways of working that improve performance and create lasting value. It highlights five key areas where innovation is making a big impact: agile and adaptive leadership, digital transformation, hybrid and remote work models, ethical and sustainable practices, and building a strong culture of learning.